Nonavailability of ultrasound: Try stethoscope in pneumatic reduction - Ramesh Tanger; Aditya Pratap Singh; Arun Kumar Gupta; Dinesh Kumar Barolia; Arvind Kumar Shukla (Wolters Kluwer Medknow Publications, 2020)
Aim and Objective: This study aimed to finding alternative ways for centers with nonavailability of ultrasonography or fluoroscopy for nonoperative pneumatic reduction of intussusceptions. Materials and Methods: A total of 48 cases of intussusceptions were included in the study in-between October 2016 and March 2018. We tried stethoscope-guided pneumatic reduction using locally assembled equipment. The intraluminal pressure was monitored and maintained below 100 mmHg. A total of two attempts of 3 min each were allowed. We compared our results with the control group who have been performing laparotomy for every case of intussusception. Results: There were 35 males and 13 females in our study. The average age of the patients was 7.5 months. Intussusceptions were reduced in 38 (80%) patients but could not be reduced in 10 (20%) patients. Majority of the intussusceptions had symptoms of at least 2 days. There were no complications such as perforation in our study. Conclusion: Stethoscope-guided pneumatic reduction seems to be a feasible and alternative effective method for the treatment of intussusceptions in children where availability of ultrasonography and skilled radiologist with overburden of work is a great issue.